Kyz ala kačuu: Kyrgyzská tradice – sociální drama – hra na pláč? - Gregorová, Barbora (Lidé města, 2024)
“Ala kachuu”, literally translated as “take and run off”, is a term used to describe the Middle Asian practice of bride kidnapping that is particularly common in Kyrgyzstan. “Ala kachuu” exists in two possible scenarios: First, the bride elopes with the man she loves while her parents oppose the marriage, or second, the non-consensual kidnapping of the bride by a stranger occurs. Both scenarios adhere to special rules and often involve the groom’s extended family and friends. Among the locals and predominantly in rural areas, “ala kachuu” continues to be part of traditional culture with roots in ancient history, as depicted in the national epic “Manas”, despite of the fact that “ala kachuu” is a criminal act often inflicting physical and psychological harm to the young woman. The following paper presents the accounts of a number of kidnappers’ strategies, provides a historical abstract, as well as giving statistics from research conducted by R. Kleinbach and L. Handrahan, and describes several actual cases of bride kidnapping.